Integrated Temperature and Heat Teaching Module for Pancasila Student Profiles to Improve Learning Outcomes - Syarifah Zaitun; Mastuang Mastuang; Saiyidah Mahtari (Universitas Lambung Mangkurat, 2026)
Physics learning in the Merdeka Curriculum still faces challenges in achieving 21st-century competencies. In many classrooms, the learning process remains dominated by lectures and formula memorization, limiting students’ opportunities to explore concepts, conduct experiments, and develop problem-solving skills. Moreover, the integration of Pancasila Student Profile values—particularly critical thinking, faithfulness and devotion to God Almighty, and collaboration—has not been clearly reflected in the available teaching materials. This gap indicates the need to develop a module that not only presents content but also encourages students to actively construct understanding through a guided inquiry approach. This study developed a heat and temperature learning module designed to address this gap. The development followed the ADDIE model and was tested on 30 high school students in Banjarmasin through expert validation, implementation observations, and learning achievement tests. The findings show that the module meets the criteria of validity, practicality, and effectiveness, with a cognitive N-Gain score of 0.47 (medium category). Thus, this module is feasible to be used as an alternative teaching material that supports more active and contextual physics learning in line with the direction of the Merdeka Curriculum. The implications of this study indicate that the integration of Pancasila Student Profile values into physics teaching modules not only contributes to improving students’ conceptual understanding but also provides a foundation for strengthening character development, such as critical reasoning, mutual cooperation, and faith-based attitudes within the learning process. Furthermore, the findings of this study can serve as a reference for teachers and instructional material developers in designing similar learning modules for other physics topics, as well as encouraging schools to implement instructional tools that align with Merdeka Curriculum policies and the reinforcement of 21st-century competencies.